Marginalization in the Colombian Criminal Law. Analysis and thoughts about pandemic context. (2021)
This article will provide data on the Colombian social reality, with which it is intended to introduce the criminal development of the circumstances of punitive mitigation enshrined in article 56 of the Colombian Penal Code, whose common denominator lies in the phenomenon of marginalization, being this the phenomenon on which it will be deepened. Based on some proposals from Latin American jurists the need to develop criteria of criminal co-responsibility, that find an anchor between criminal dogmatics and the context of its application will be justified.